2014
DOI: 10.1093/conphys/cou026
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying long-term stress in brown bears with the hair cortisol concentration: a biomarker that may be confounded by rapid changes in response to capture and handling

Abstract: We evaluated the effects of several factors on the cortisol concentration of hair in wild brown bears. Our findings suggest the cortisol concentration may increase quickly following capture, even after hair growth has ceased. We emphasize the need for more validation of this measure as an indicator of long-term stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 75 publications
(98 reference statements)
3
91
1
Order By: Relevance
“…For example, Cattet et al . (2014) showed that hair cortisol levels varied between capture methods and were elevated in captured animals even in the hair's quiescent (non-growing) phase (Cattet et al ., 2014). If faecal and hair cortisol are not derived from the same source, one would not expect GC levels in these substrates to correlate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cattet et al . (2014) showed that hair cortisol levels varied between capture methods and were elevated in captured animals even in the hair's quiescent (non-growing) phase (Cattet et al ., 2014). If faecal and hair cortisol are not derived from the same source, one would not expect GC levels in these substrates to correlate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is usually a lag between observed of peaks in blood GC concentrations and faecal GC metabolite levels (Touma and Palme, 2005). Glucocorticoids in hair are assumed to be deposited from unbound cortisol in the blood while the hair is growing, potentially representing stress over several months (Sheriff et al ., 2011), but may also be derived from local excretions from the skin (Cattet et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…There is empirical evidence that in certain conditions, those hosts that are more exposed to parasites (LoGiudice, ) or that have increased parasitic loads (Craig, Jones, Pilkington, & Pemberton, ; Craig, Pilkington, & Pemberton, ; Pulkkinen & Ebert, ) are also at higher risk of mortality. Many studies have explored aspects of parasitism‐led mortality using analytical and theoretical methods (Anderson & Gordon, ; Anderson & May, ; Best & Hoyle, ; Cattet et al., ; May & Anderson, ; Miller, White, & Boots, ; Rousset, Thomas, Meeûs, & Renaud, ; Wilber, Weinstein, & Briggs, ). Additionally, general associations between mortality and parasitism have been studied experimentally in model systems such as fruit flies, Drosophila spp.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, since the early 2000s, awareness of capture and tagging-related effects on animals has grown with researchers using various approaches to tackle potential problems (McMahon et al 2011;Vandenabeele et al 2015;White et al 2013). While some studies found no evidence for such effects (McMahon et al 2008;Ropert-Coudert et al 2009), others showed tagging-related impacts ranging from physiological effects, such as changes in cortisol levels (Cattet et al 2014) or capture myopathy (Höfle et al 2004;Ponjoan et al 2008), to behavioural effects including changes in movement and space use (Morellet et al 2009;Rachlow et al 2014) or generally reduced activity (Broell et al 2016;Dennis and Shah 2012). Tagging effects may accumulate over time and can have detrimental influence on life history parameters such as reproductive success or survival rate (Barron et al 2010;Blanchet et al 2014;Casas et al 2015), or may only be shorttermed and diminish over time (Dennis and Shah 2012;Morellet et al 2009).…”
Section: Introductionmentioning
confidence: 99%